STRENGTHENING STRATEGIC HUMAN RESOURCE MANAGEMENT THROUGH LECTURER PERSONAL MANAGEMENT: EVIDENCE FROM HIGHER EDUCATION INSTITUTIONS - Aip Syarifudin; Dewi Nurdiyanti; Euis Komala; Lanlan Muhria; Eka Zahra Nabila Nakhwa (Universitas Labuhanbatu, 2026)
Purpose – This study examines the impact of Lecturer Personal Management (LPM) on strengthening Strategic Human Resource Management (SHRM) in higher education. The main aim of this research is to identify the barriers to the effective development of academic human resources.Methodology – A mixed-methods approach was adopted, specifically the sequential explanatory design. The quantitative element consisted of administering a structured self-completion questionnaire to a sample of 80 lecturers from five purposively sampled higher education institutions in Tanzania. In the qualitative component, semi-structured interviews were conducted with eight key informants, who were lecturers and heads of study programs, as well as academic leaders and HR managers. The research instruments included frameworks for measuring Lecturer Personal Management and Strategic Human Resource Management. Quantitative data were subjected to descriptive analysis, while qualitative data were analyzed by theme.Findings – The findings emphasize that Lecturer Personal Management comprises six critical dimensions: professional competence, academic career development, work motivation, tridharma productivity, institutional commitment, and adaptability. Although all dimensions were critical to the implementation of SHRM, adaptability, work motivation, professional competence, and institutional commitment were considered the strongest. The primary enabling factors included leadership support, engagement with the academic culture, professional collaboration, and access to training and career development. In contrast, the primary hindering factors included workload demands, inadequate resources, technology gaps, policy changes, and low motivation. The study also introduced the Lecturer Personal Management Framework (LPMF), comprising the following components: Input, Process, Output, Outcome, and Impact. The findings indicated that successful implementation of SHRM focuses more on lecturers’ ability to manage their career development than on the institution's systems and policies.Contribution – The study contributes to the body of knowledge on educational management by elaborating Human Capital Theory and Strategic Human Resource Management Theory through the Lecturer Personal Management Framework. This framework describes the interaction between lecturer-level resources and the institution's support in strengthening SHRM within higher education.